A new species of the genus Luzulaspis (Hemiptera: Coccomorpha: Coccidae) from Hokkaido Island, Japan - Tanaka, Hirotaka; Sasaki, Daisuke; Kamitani, Satoshi (Zootaxa, 2021)
A new species of soft scale insect (Hemiptera: Coccomorpha: Coccidae), Luzulaspis kinakikir Tanaka sp. nov., collected from Carex miyabei (Cyperaceae), on Hokkaido Island, Japan, is described and illustrated based on adult female morphology. The new species, which belongs to the Scotica group of Luzulaspis, is similar to L. filizae Kaydan, 2015, but can be distinguished from it by possessing multilocular pores with fewer loculi; numerous dorsal tubular ducts, obviously wider than the ventral tubular ducts, and by lacking dorsal tubular ducts on the head apex. An updated diagnosis of Luzulaspis and two identification keys, one to the Japanese species of Luzulaspis and the other to the species of the Scotica group of Luzulaspis, are provided.